Mathematical model of heat supply installation as an object of economic efficiency and automation (Computer systems and information technologies, 2021)
Solar energy is widely used in cases where the inaccessibility of other energy sources in combination with a sufficient amount of solar radiation justifies it economically. With the help of a system of solar collectors, you can significantly reduce energy costs for hot water supply and heating. In addition, the use of this system helps reduce CO2 emissions. The potential of solar energy in Ukraine is quite high. According to the climatic conditions of our region, solar activity is slightly lower thanin the southern regions, so the use of flat solar collectors, which use both direct and scattered solar radiation, is effective for our region. The use of heat collectors in the home for water supply and heating of small areas is economically feasible, as it does not require significant costs. Heat supply plants using non-traditional energy sources are promising in terms of fuel savings and reduction of harmful effects on the environment. To increase the service life, economical use of heat and fuel, efficient operation of the installation requires the use of automation. The article considers the development of a mathematical model of a heat supply installation based on a solar collector. For automated control of the heat supply installation, it is necessary to know the properties of this installation as a whole and its individual elements. For this purpose, models of individual elements of the heat supply installation in a linear approximation are considered. The solar collector is conditionally divided into two parts. The model of the ground heat exchanger is developed. Also e battery models and consumer premises. The given matrices of elements of installation of heat supply are united in the uniform system of matrices. The obtained results allow estimating in advance efficiency of their use and economic attractiveness.
Keywords: modeling; heat supply; matrix